Changes in Appetite-Dependent Hormones and Body Composition After 8 Weeks of High-Intensity Interval Training and Vitamin D Supplementation in Sedentary Overweight Men - Sheikholeslami-Vatani, Dariush; Rostamzadeh, Naser (Frontiers in Nutrition, 2022)
Exercise and diet are important factors for energy balance and appetite regulation. The aim of this study was to investigate the effect of 8 weeks High Intensity Interval Training (HIIT) and vitamin D3 supplementation in sedentary overweight men. Forty-eight participants were randomly assigned to one of the following four groups (n = 12): HIIT + VitD, HIIT + placebo (3 sessions per week, 10 × 1 min interval cycling at 90–100% VO2peak separated by 1 min active recovery at 15% VO2peakfor 8 weeks), Vit D and control groups. Participants received 2,000 IU/day 25 (OH) D3 or placebo. Measurements were taken pre and post training after 10 h overnight fasting. Insulin, weight, BMI and body fat percentage were significantly decreased, but PYY was significantly increased in the HIIT + Vit D and HIIT + placebo groups (p = 0.001 and p = 0.001, respectively) after 8 weeks of HIIT. Insulin (p = 0.009, p = 0.001), weight, BMI and body fat percentage (p = 0.001, p = 0.001) were significantly lower in the HIIT + Vit D and HIIT + placebo groups compared to the Vit D and control groups. However, PYY was significantly higher in the HIIT + Vit D group compared to the Vit D (p = 0.025) and control groups (p = 0.007) and also in the HIIT + placebo group compared to the Vit D (p = 0.037) and control groups (p = 0.032) after 8 weeks of HIIT. The combination of regular HIIT with vitamin D supplementation has a effect on appetite control and body composition.